The Effect of Using Japanese Music in Improving Motivation to Learn Japanese - Nurhaliza, Zalfaa; Aneros, Noviyanti; Sugihartono, Sugihartono (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2024)
Language education is a crucial element in foreign language learning, where motivation plays a key role in student success. Strong motivation is a key factor in achieving success in learning a foreign language, and the use of Japanese music is considered a potential way to increase motivation for learning Japanese. This study proposes to explore the effect of using Japanese music as a motivational tool in learning Japanese. By clarifying the impact of Japanese music on students' motivation levels, this study hopes to provide better insight into the relationship between music use and Japanese language learning. The research also involved analyzing the participant's responses to the use of Japanese music in language learning. This study has potential benefits in improving the understanding of the factors that influence the motivation of Japanese language learners. The results of this study are expected to provide new insights for more effective teaching approaches, provide practical guidelines for teachers, and enrich the Japanese language learning experience through a holistic approach involving music. As such, this research is expected to bring positive benefits to Japanese language learners and support the development of foreign language education as a whole.